CYBER CULTURE OF SOCIAL MEDIA: IDENTITY AS TRASH OF INFORMATION - 'Uyun, Zafirah Quroatun; hakim, lukman (IAIN Syekh Nurjati Cirebon, 2020)
AbstractThis article goes from the disturbing anxiety of social media users to cyber culture such as phenomenon of trash information. Some social media users feel necessary to reveal true identity while others insult identity as something that the public will never know. While in communication there are no messages in the media that contain no meaning and no messages distributed without purpose. Even though the purpose of communication is different, the purpose of information even if it is mere text. In the case of social media, these messages distort more than just meaning. With observation methods and discourse analysis knife, the research found that cyber culture in social media is more than a form of information trash because of overlapping of information is particularly unclear of user identity. The study tried to see interesting phenomena that occur especially with regard to virtual/online and real-world/offline communication patterns. Social media at some point is a place where they can be identified or just a stockpile of inconclusive information. By combining cyber cultural concept and information sircuit, this research also found of identity ambivalence in social media that end by trash of information.